(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article analyzes effective ways to increase the culture of using Social Networks. At the same time, the article developed proposals aimed at preventing slouchy information attacks, a threat to the consciousness and lifestyle of young people through Social Network.